'Are decisions about discharge of elderly hospital patients mainly about freeing blocked beds?' A qualitative observational study. Issue 6 (19th November 2012) - Ekdahl, Anne Wissendorff; Linderholm, Märit; Hellström, I; Andersson, Lars; Friedrichsen, Maria
Abstract : Objective: To explore the interactions concerning the frail and elderly patients having to do with discharge from acute hospital wards and their participation in medical decision-making. The views of the patients and the medical staff were both investigated. Design: A qualitative observational and interview study using the grounded theory. Setting and participants: The setting was three hospitals in rural and urban areas of two counties in Sweden of which one was a teaching hospital. The data comprised observations, healthcare staff interviews and patient interviews. The selected patients were all about to be informed that they were going to be discharged. Results: The patients were seldom invited to participate in the decision-making regarding discharge. Generally, most communications regarding discharge were between the doctor and the nurse, after which the patient was simply informed about the decision. It was observed that the discharge information was often given in an indirect way as if other, albeit absent, people were responsible for the decision. Interviews with the healthcare staff revealed their preoccupation with the need to free up beds: 'thinking about discharge planning all the time' was the core category. This focus not only failed to fulfil the complex needs of elderly patients, it also generated feelings of frustration and guilt in the staff, and made the patients feel unwelcome. Conclusions: Frail elderly patients often did not participate in the medical decision-making regarding their discharge from hospital. The staff was highly focused on patients getting rapidly discharged, which made it difficult to fulfil the complex needs of these patients.